Arctic cod (Boreogadus saida, Gadidae) in the Chukchi Sea and adjacent waters - A. B. Savin (Известия ТИНРО, 2021)
Biology, spatial distribution, migrations, and stock dynamics are considered for arctic cod in the Russian sector of the Chukchi Sea and adjacent waters of the northern Bering Sea on the data of trawl surveys conducted by Pacific Res. Inst. of Fisheries and Oceanography (TINRO) in 1971–2020, fishery statistics and cited data. Active fishery of arctic cod occurred in late 1960s — early 1970s and in 1980s, when annual catch of this species reached 24,500 t. Mean size of arctic cod in trawl catches increased southward with decreasing of the underyearlings portion; the mean size was larger in catches of bottom trawl than in catches of midwater trawl because of the same reason. The females became adult from the size 11–12 cm, the males — from the size 8–9 cm. Diet of arctic cod included benthos and plankton, as well as juvenile fish. Spawning of arctic cod in the Chukchi Sea in summer-autumn was never observed, but some fish ready to spawn were found in the Bering Strait in this season. Arctic cod aggregated in the coastal zone of the southern Chukchi Sea in August, then partially migrated to the Bering Sea through the Bering Strait in September-November. The portion of the Chukchi Sea stock involved into this migration depended on fall oceanographic conditions — it was considerably larger in cold years with early freezing of the sea. Back migration from the Bering Sea to Chukchi Sea depended on spring environments — only a part of the fish of Chukchi Sea origin returned back in cold years with late ice melting and the rest spawned in the Bering Sea, whereas almost all the fish returned to the Chukchi Sea for spawning in warm years with early melting. The stock of arctic cod in the western Chukchi Sea varied in 1971–2020 between 3.5–396.5 . 103  t, on average 80.6 . 103  t in the bottom layer, and between 4.0–329.2 . 103  t, on average 150.6 . 103  t in the upper layer.